Constitutional Reform as Neoliberal Trojan Horse: The Politics of New Constitutionalism in the Global South - Anggoro, Syahriza Alkohir (Hang Tuah Law Journal, 2025)
The increasing trend of constitutional reform in the global South for the last three decades has marked a shift from the state interventionism regime to free market neoliberalism. This article explores the concept of new constitutionalism which has been used in comparative constitutional law studies to understand the adoption of neoliberal legal norms through constitutional reform. It argues that the constitutionalization of neoliberal features cannot be separated from the context of the global imperialism hegemony which has an interest to establish a market-friendly legal framework in global South. Incorporating neoliberal legal norms into the economic constitution at the national level offers an effective way to lock in neoliberal value as a normative order for the state institutions and therefore, that place limitation of state intervention toward market.